Calibration of Echo Sounders for Offshore Sounding Using Temperature and Depth - Calder, M. (The International Hydrographic Review, 2015)
One of the difficulties confronting hydrographic surveyors in the past lias been that of calibrating echo sounders to compensate for the varying velocity of sound in the water column. Mechanical methods such as bar checks, whilst adequate for shallow water bathymetry, were impractical and inaccurate for depths in excess of about 30 metres. This paper outlines a new and more satisfactory technique.